HARMONISASI KEBIJAKAN PENGENTASAN KEMISKINAN DI INDONESIA YANG BERORIENTASI PADA MILLENNIUM DEVELOPMENT GOALS - Emmy Latifah (Jurnal Dinamika Hukum, 2011)
The purpose of this research is to understand the level of harmonization of poverty alleviation regulations and policies in Indonesia within the Millennium Development Goals (MDGs), especially Target 1. From this research, it can be created a model of regulation and polices harmonization of poverty alleviation in Indonesia in order to harmony with the MDGs. To achieve these objectives, data collected by regulation and policies of poverty alleviation in Indonesia, and then it is analyzed with editing analysis style. The results of this research are the policies of poverty alleviation in Indonesia are not harmonious with the MDG target. It is because of the poverty alleviation policies in Indonesia with the MDG target as a result of differences in defining poverty, which is not focused on the definition of poverty used by the MDGs. The definition of poverty according to the MDGs is those who have income less than US$ 1 per day.  Key words: harmonization of regulations and policies, poverty alleviation, Millennium Development Goals